Disordered Money Behaviors: Development of the Klontz Money Behavior Inventory - Bradley Klontz; Sonya L Britt; Kristy L Archuleta; Ted Klontz (Journal of Financial Therapy, 2012)
Much of the existing literature on financial behavior focuses on basic money management tasks (e.g., balancing a checkbook). However, it can be equally important to identify problematic financial behaviors that can sabotage one’s financial health. The purpose of this study was to create an assessment tool that can be used by mental health and financial professionals to identify disordered money behaviors that may impede on progress towards one’s financial goals. This study asked 422 respondents to indicate their agreement with disordered money behaviors, including compulsive buying, pathological gambling, compulsive hoarding, workaholism, financial enabling, financial dependence, financial denial, and financial enmeshment, which were correlated with demographic characteristics and financial outcomes. The results identified eight subscales derived from 68 disordered money behavior items. All eight subscales were found to have high reliability in measuring disordered behaviors, and six were associated with negative financial health indicators (e.g. less net worth, less income, and/or more revolving credit).
Keywords: financial therapy; mental health; financial planning; financial counseling